1988
DOI: 10.1002/bio.1170020205
|View full text |Cite
|
Sign up to set email alerts
|

The transcription of bacterial luminescence is regulated by sigma 32

Abstract: Luminescence in the marine bacterium, Vibrio fischeri, is regulated by a small molecule, the autoinducer. The transcription of the V. fischeri lux genes also requires a regulatory protein, (luxR), cAMP and CRP. We show that, apart from these components, the transcription of the PR lux operon is also controlled by the activity of sigma 32 (htpR protein). In luminescent Escherichia coli (E. coli/pChv1), as well as in different marine luminous bacteria and their naturally occurring dark (K) variants, the luminesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
37
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…An increase in 3-galactosidase activity of about 250% was observed in C600/pTRZ cells grown in LB for 3 h in the presence of 1.5 to 2.5% ethanol (data not shown). Similar results were observed with E. coli/pChvl cells (25).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…An increase in 3-galactosidase activity of about 250% was observed in C600/pTRZ cells grown in LB for 3 h in the presence of 1.5 to 2.5% ethanol (data not shown). Similar results were observed with E. coli/pChvl cells (25).…”
Section: Resultssupporting
confidence: 88%
“…This (24,25). We also demonstrated that stress conditions, such as ethanol treatment or starvation, resulted in strong induction of 0-galactosidase activity in E. coli harboring the plasmid pTRZ and in luciferase formation in E. coli/pChvl cells (25).…”
Section: Resultsmentioning
confidence: 58%
See 3 more Smart Citations